1994
DOI: 10.1111/j.1476-5381.1994.tb17147.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory 5‐hydroxytryptamine receptors involved in pressor effects obtained by stimulation of sympathetic outflow from spinal cord in pithed rats

Abstract: 1 A study was made of the effects of 5-hydroxytryptamine (5-HT) on pressor response induced in vivo by electrical stimulation of the sympathetic outflow from the spinal cord of pithed rats. All animals had been pretreated with atropine. Intravenous infusion of 5-hydroxytryptamine at doses of 10 and 20 jig kg-' min-' reduced the pressor effects obtained by electrical stimulation at intervals of 10 min over the 1 h of infusion. 2 This inhibitory action of 5-HT was depressed by cyproheptadine and methiothepin but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 37 publications
6
35
0
Order By: Relevance
“…Furthermore, the most likely locus of the above 5-HT 1D receptors could be prejunctionally on sympathetic periarterial renal nerves. Although we have no direct evidence to unequivocally support this localization, it is noteworthy that L-694,247 failed to affect the vasopressor responses to exogenous norepinephrine (see above), as reported for prejunctional sympathetic-inhibitory 5-HT 1D receptors [9,13,15] in the pithed rat model. Consistent with this suggestion, other findings have detected the presence of 5-HT 1D receptor type in sympathetic nerve endings [32,33], as well as in canine kidney cells [34].…”
Section: The Role Of Prejunctional Receptors In the Inhibition Of Thementioning
confidence: 57%
See 4 more Smart Citations
“…Furthermore, the most likely locus of the above 5-HT 1D receptors could be prejunctionally on sympathetic periarterial renal nerves. Although we have no direct evidence to unequivocally support this localization, it is noteworthy that L-694,247 failed to affect the vasopressor responses to exogenous norepinephrine (see above), as reported for prejunctional sympathetic-inhibitory 5-HT 1D receptors [9,13,15] in the pithed rat model. Consistent with this suggestion, other findings have detected the presence of 5-HT 1D receptor type in sympathetic nerve endings [32,33], as well as in canine kidney cells [34].…”
Section: The Role Of Prejunctional Receptors In the Inhibition Of Thementioning
confidence: 57%
“…5-HT seems to modulate adrenergic neurotransmission, leading to sympatho-excitatory or sympatho-inhibitory effects, and, consequently, into vasopressor and tachycardic or vasodepressor and bradycardic responses, respectively [9,13,15,16]. In this sense, some studies by our research team and others have suggested that 5-HT 1 receptor mediates inhibition of the sympathetic neurotransmission [9][10][11][12][13]17,18].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations